Equipment review: Intrahospital transport of critically ill patients - Waydhas, Christian (BioMed Central, 1999)
BACKGROUND: This review on the current literature of the intrahospital transport of critically ill patients addresses type and incidence of adverse effects, risk factors and risk assessment, and the available information on efficiency and cost-effectiveness of transferring such patients for diagnostic or therapeutic interventions within hospital. Methods and guidelines to prevent or reduce potential hazards and complications are provided. METHODS: A Medline search was performed using the terms 'critical illness', 'transport of patients', 'patient transfer', 'critical care', 'monitoring' and 'intrahospital transport', and all information concerning the intrahospital transport of patients was considered. RESULTS: Adverse effects may occur in up to 70% of transports. They include a change in heart rate, arterial hypotension and hypertension, increased intracranial pressure, arrhythmias, cardiac arrest and a change in respiratory rate, hypocapnia and hypercapnia, and significant hypoxaemia. No transport-related deaths have been reported. In up to one-third of cases mishaps during transport were equipment related. A long-term deterioration of respiratory function was observed in 12% of cases. Patient-related risk indicators were found to be a high Therapeutic Intervention Severity Score, mechanical ventilation, ventilation with positive end-expiratory pressure and high injury severity score. Patients' age, duration of transport, destination of transport, Acute Physiology and Chronic Health Evaluation II score, personnel accompanying the patient and other factors were not found to correlate with an increased rate of complications. Transports for diagnostic procedures resulted in a change in patient management in 40-50% of cases, indicating a good risk:benefit ratio. CONCLUSIONS: To prevent adverse effects of intrahospital transports, guidelines concerning the organization of transports, the personnel, equipment and monitoring should be followed. In particular, the presence of a critical care physician during transport, proper equipment to monitor vital functions and to treat such disturbances immediately, and close control of the patient's ventilation appear to be of major importance. It appears useful to use specifically constructed carts including standard intensive care unit ventilators in a selected group of patients. To further reduce the rate of inadvertent mishaps resulting from transports, alternative diagnostic modalities or techniques and performing surgical procedures in the intensive care unit should be considered.